Expanding the Use of Ex Situ Organ Machine Perfusion Beyond Transplantation - Martins, Paulo N.; Edil, Barish H.; McNally, Lacey; Battula, Narendra R. (Artificial organs, 2025)
ABSTRACT Machine perfusion preservation of grafts has become the gold standard organ preservation method. It has been developed to improve the quality of grafts due to the increasing gap between demand and supply of organs for transplantation. Following successful long‐term machine perfusion preservation with automated commercial devices developed for preservation of organs for transplantation, there is increasing interest in utilizing perfused discarded human organs and xenografts for a variety of purposes beyond transplantation including gene therapy and modulation, drug testing, chemotherapy, ex vivo surgery, organ supporting systems, bioengineering, and surgical training and education. Here, we review all current and potential applications of machine perfusion preservation. Machine perfusion preservation of grafts has become the gold standard organ preservation method. There is increasing interest in utilizing perfused discarded human organs for a variety of purposes beyond transplantation, including gene therapy and modulation, drug testing, chemotherapy, ex vivo surgery, bioengineering, and surgical education/training. Here, we review all current and potential applications of machine perfusion preservation.